Knowledge of Green Practices Adoption and Infusion among Employees’ of Selected Manufacturing Firms in Ogun State, Nigeria - Oludele Mayowa Solaja; Obatunde Bright Adetola (Sriwijaya Journal of Environment, 2020)
This study investigates the knowledge of green practices adoption and infusion among employees of selected manufacturing companies in Ogun State, Nigeria. The study adopts a descriptive design in which qualitative (in-depth interview and key informant interview guide) and quantitative (questionnaire) methods were used for data collection. Multistage sampling techniques were employed in selecting respondents for the study. A total of 321 respondents were utilized in gathering the quantitative data while four (4) key informant interviews and eight (8) in-depth interviews were used for the collection of qualitative data. Descriptive statistics (frequency count and percentage distribution) and qualitative content analysis were deployed in analysing the data. The socio-demographic of the respondents showed that all had some level of formal education.  The findings of the study also revealed that a majority (84.7%) of the respondents had some level of knowledge about green practices adoption and infusion in their organizations however a significant proportion (15.3%) of the respondents are still lacking sufficient understanding of green practices adoption and infusion as indicated in the study organizations. The study therefore concludes that improved awareness and education on every aspect of green practices infusion and adoption is still needed among employees of manufacturing companies in Nigeria in order to achieve the desired sustainable development goals by the year 2030.